The Time Dependent Pricing (TDP) by Mobile Network Operators using Broad Band Pricing Systems - Venugopal, A; Niranchana, D (International Journal of Computer Sciences and Engineering, 2019)
The pricing schemes that are in practice today and analyze why they do not solve the ISPs problem from the growing data traffic. The Internet can incentivize users to spread out their bandwidth consumption more evenly across different times of the day, and thus help ISPs to overcome the problem of peak congestion. Congestion pricing is not a new idea in itself, but for IP network data plan we learn from our wired and wireless ISP collaborators that the time for its implementation has finally arrived.